TINJAUAN KRITIS TERHADAP KONSEP IDEOLOGIS KEPENGARANGAN INDONESIA : KAJIAN SOSIOLOGIS - Suyadi Nfn (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Indonesian writers continue to race across the ocean of globalization and technology. Those who come from various regions, fused into a large community as citizens of the world literature, sow among a number of mirage and cyberspace. An Indonesia poet or author has diverse languages, in accordance with the ideological background (worldview) authorship respectively. Ideology means a way of thinking or way of life of a person or a group. This paper assesses the ideology of Indonesia authorship in terms of sosilogi. Sociology is the study of society or community. Through this sociological theory discovered the concept of Indonesian author diverse ideologies. Indonesian author is able to create an ideology novelty literary language in conditions of globalization regime. Through literature, the authors of Indonesia express ideas and thoughts for the people of Indonesia.